Convergence Between a New EU Economic Diplomacy and International Business Strategies - Nicoleta Vasilcovschi (CES Working Papers, 2016)
Economic diplomacy is known as a symbol of the European Union and represents its primary function. With the development of science and new ways of communication, the European Union can organize a new approach for its economic diplomacy. The main advantage of the European Union as a soft power is that its economic and diplomatic interests are represented in a manner that is based not on confrontation but economic collaboration with other states. The disadvantage is that this domain is presently not used enough to represent EU interests. This paper describes economic diplomacy in general and the economic diplomacy of the EU in particular. Divided into three parts, the goal of this study is to outline the importance of economic diplomacy, its evolution, the influence of this domain on the creation of previous economic treaties, and its possible future impact on the development of new agreements between the European Union and its neighbour countries.The main methodology used is descriptive, presenting the evolution of this field and the new business strategies that can be used to improve cooperation at the eastern border of the European Union. Therefore here are presented the historical background of EU Economic diplomacy, its present issues and future challenges. The quantitative data used in this research paper are based on information from the EU website and on the actual events concerning debates about economic diplomacy and its future. The research questions presented herein follow the general evolution of this domain and its mutual influence with EU's businesses strategies.
Keywords: F5; Z00; 330; economic diplomacy; business strategies; business diplomacy; European Union